PENYISIHAN PARAMETER PENCEMAR AIR PERMUKAAN DENGAN MOBILE WATER TREATMENT - Firra Rosariawari; Aulia Ulfah Farahdiba (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
The need for clean water quantitatively and qualitatively is needed in daily life. The increasing pollution of surface water results in a decrease in water quality. This research designs a simple surface water treatment unit into clean water. So that people can easily get clean water directly. With several units made in Mobile Water Treatment, it is expected to meet the needs of clean water in accordance with clean water quality standards. The clean water treatment process in this study uses several processing units designed in one Mobile Water Treatment unit package. The process in the Mobile Water Treatment Unit is a coagulation process using parshall flume, a flocculation process using a baffle channel, a reservoir to precipitate the results of the flocculation process and followed by an adsorption process using activated carbon and silica and a disinfectant. To determine the effectiveness of the Mobile Water Treatment unit package, it is necessary to test each unit. The coagulation, flocculation, sedimentation and adsorbs units have been tested, in this study it will be continued with a disinfection unit. The effectiveness of the disinfection unit will be tested by using several variations of exposure time to get the right detention time. The capacity of this unit is 120 L with a discharge of 9 L/minute and the coagulant used is PAC with a concentration of 75 mg/L. 32 of 2017. The pollutant parameters to be analyzed are TSS, TDS, Turbidity, Fe, Mn, pH, hardness and permanganate